Sumergidos en el juego y la lectura. El juego teatral como herramienta didáctica para el desarrollo de la decodificación secundaria del proceso lector. (2022)
The present systematical data collection is supported by the implementation of different theater games in educative contexts. They were developed in order to strengthen the components belonging to the secondary decoding that are called: • Punctuation: revels the importance of punctuation marks in the reading process is addressed. • Pronominalization: it is suitable to deal with pronouns and their function in reading • Chromatization: shows the emphasis or meanings worked on in the texts • Propositional inference: a component in which the intentions found in a text are approached and identified. In addition, the game was used to stand out as a functional tool in the classroom, nurturing the teaching-learning processes